HYDROGEN-ISOTOPE ANALYSIS OF POTENTIALLY TOXIC ORGANIC MATERIALS EMPLOYING MANGANESE REDUCTION AND DISPOSABLE NICKEL-PYROLYSIS TUBES - Motz J.E.; Shouakar-Stash O.; Drimmie R.J.; Edwards T.W.D.; Frape S.K.; Annable W.K. (My University, 2001)
Use of a simple, disposable apparatus allows the measurement of 2H/1H ratios in small quantities of potentially toxic organic materials without the release of hazardous compounds. The apparatus consists of welded nickel pyrolysis bombs encased in quartz breakseals. Samples are enclosed in the bombs with a manganese-reducing agent. Hydrogen diffuses through the nickel upon heating and is captured in the quartz envelope for analysis. Tests with standard polyethylene foil and cystine, as well as with water and several herbicides, show that this method produces good precision (typically between +/-1.0%% and +/-4.0%%) and is equally applicable to solid and liquid materials.
Keywords: HYDROGEN; ISOTOPES; ORGANIC; TOXIC MATERIALS; WATER